Calabi-Yau Threefolds in Weighted Flag Varieties - Muhammad Imran Qureshi; Balázs Szendrői (Advances in High Energy Physics)
We review the construction of families of projective varieties, in particular Calabi-Yau threefolds, as quasilinear sections in weighted flag varieties. We also describe a construction of tautological orbibundles on these varieties, which may be of interest in heterotic model building.